Preoperative visualization of congenital lung abnormalities: hybridizing artificial intelligence and virtual reality. (16th January 2023) - Bakhuis, Wouter; Kersten, Casper M; Sadeghi, Amir H; Mank, Quinten J; Wijnen, René M H; Ciet, Pierluigi; Bogers, Ad J J C; Schnater, J Marco; Mahtab, Edris A F
Abstract: OBJECTIVES: When surgical resection is indicated for a congenital lung abnormality (CLA), lobectomy is often preferred over segmentectomy, mostly because the latter is associated with more residual disease. Presumably, this occurs in children because sublobar surgery often does not adhere to anatomical borders (wedge resection instead of segmentectomy), thus increasing the risk of residual disease. This study investigated the feasibility of identifying eligible cases for anatomical segmentectomy by combining virtual reality (VR) and artificial intelligence (AI). METHODS: Semi-automated segmentation of bronchovascular structures and lesions were visualized with VR and AI technology. Two specialists independently evaluated via a questionnaire the informative value of regular computed tomography versus three-dimensional (3D) VR images. RESULTS: Five asymptomatic, non-operated cases were selected. Bronchovascular segmentation, volume calculation and image visualization in the VR environment were successful in all cases. Based on the computed tomography images, assignment of the CLA lesion to specific lung segments matched between the consulted specialists in only 1 out of the cases. Based on the three 3D VR images, however, the localization matched in 3 of the 5 cases. If the patients would have been operated, adding the 3D VR tool to the preoperative workup would have resulted in changing the surgical strategy (i.e. lobectomy versus segmentectomy) in 4 cases. CONCLUSIONS: This study demonstrated the technical feasibility of a hybridized AI–VR visualization of segment-level lung anatomy in patients with CLA. Further exploration of the value of 3D VR in identifying eligible cases for anatomical segmentectomy is therefore warranted. Abstract : Congenital lung abnormalities (CLA) are developmental pulmonary lesions, which comprise, among others, congenital pulmonary airway malformation (CPAM), bronchopulmonary sequestration (BPS), bronchogenic cyst and congenital emphysema.